2020
DOI: 10.1093/femsle/fnaa038
|View full text |Cite
|
Sign up to set email alerts
|

Zinc can counteract selection for ciprofloxacin resistance

Abstract: Antimicrobial resistance (AMR) has emerged as one of the most pressing threats to public health. AMR evolution occurs in the clinic but also in the environment, where antibiotics and heavy metals can select and co-select for AMR. While the selective potential of both antibiotics and metals is increasingly well-characterized, experimental studies exploring their combined effects on AMR evolution are rare. It has previously been demonstrated that fluoroquinolone antibiotics such as ciprofloxacin can chelate meta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…Comparatively, the concentrations of bio-Cu and bio-Zn in the AMX group were slightly higher than those in the CK group during the early stage of composting. This difference indicated that the addition of AMX likely hindered the passivation process of HMs and, thus, increased the risks of HMs contamination and the co-selection pressure of inducing bacterial resistance, which was also confirmed by previous reports ( Song et al, 2017 ; Vos et al, 2019 ).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Comparatively, the concentrations of bio-Cu and bio-Zn in the AMX group were slightly higher than those in the CK group during the early stage of composting. This difference indicated that the addition of AMX likely hindered the passivation process of HMs and, thus, increased the risks of HMs contamination and the co-selection pressure of inducing bacterial resistance, which was also confirmed by previous reports ( Song et al, 2017 ; Vos et al, 2019 ).…”
Section: Resultssupporting
confidence: 85%
“…With the overuse, misuse, and abuse of antibiotics in modern medicine and the livestock industry in the last decades ( Yao L. et al, 2020 ; Zhang et al, 2020 ; Zou et al, 2020 ; Wang et al, 2021 ), antimicrobial resistance has developed into one of the most urgent public health crises in recent years ( Zhu et al, 2017a ; Vos et al, 2019 ; Joshi and Kim, 2020 ; Dai et al, 2022 ). According to statistics, the global defined daily doses of antibiotics reached 34.8 billion in 2015 and have increased by 65% since 2000 ( Zhao R. et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in the presence of ZnO and Cu-ZnO, the formation of Cipro-Zn chelates occurred, which are desirable species because they prevent bacterial selection for resistance 57 . In addition, CIPRO-Zn exhibited efficient photodegradation under UV light exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is used in numerous cosmetic products as an antioxidant, antiaging, antimicrobial, and anti-inflammatory agent (Abendrot & Kalinowska-Lis, 2018). In a single-species competition experiment, zinc increased the MSC of ciprofloxacin by fivefold, suggesting that zinc and ciprofloxacin behave antagonistically (Vos et al, 2020).…”
Section: Co-selectionmentioning
confidence: 99%